The α2B‐adrenergic receptor is mutant in cortical myoclonus and epilepsy. Issue 1 (2nd January 2014) - De, Maurizio; Vago, Riccardo; Striano, Pasquale; Di, Carlo; Zara, Federico; Mei, Davide; Kim, Min Seuk; Muallem, Shmuel; Chen, Yunjia; Wang, Qin; Guerrini, Renzo; Casari, Giorgio
<x xml:space="preserve">Abstract</x> Objective Autosomal dominant cortical myoclonus and epilepsy (ADCME) is characterized by distal, fairly rhythmic myoclonus and epilepsy with variable severity. We have previously mapped the disease locus on chromosome 2p11.1‐q12.2 by genome‐wide linkage analysis. Additional pedigrees affected by similar forms of epilepsy have been associated with chromosomes 8q, 5p, and 3q, but none of the causing genes has been identified. We aim to identify the mutant gene responsible for this form of epilepsy. Methods Genes included in the ADCME critical region were directly sequenced. Coimmunoprecipitation, immunofluorescent, and electrophysiologic approaches to transfected human cells have been utilized for testing the functional significance of the identified mutation. Results Here we show that mutation in the α2‐adrenergic receptor subtype B (α2B‐AR) is associated with ADCME by identifying a novel in‐frame insertion/deletion in 2 Italian families. The mutation alters several conserved residues of the third intracellular loop, hampering neither the α2B‐AR plasma membrane localization nor the arrestin‐mediated internalization capacity, but altering the binding with the scaffolding protein spinophilin upon neurotransmitter activation. Spinophilin, in turn, regulates interaction of G protein coupled receptors with regulator of G protein signaling proteins. Accordingly, the mutant α2B‐AR increases the epinephrine‐stimulated calcium signaling. Interpretation The identified mutation is responsible for ADCME, as the loss of α2B‐AR/spinophilin interaction causes a gain of function effect. This work implicates for the first time the α‐adrenergic system in human epilepsy and opens new ways of understanding the molecular pathway of epileptogenesis, widening the spectrum of possible therapeutic targets. ANN NEUROL 2014;75:77–87